THE BASIC MOVEMENT OF BASKETBALL MOVEMENT THROUGH APPLICATION OF MODEL PERSONALIZED SYSTEM OF INSTRUCTION (PSI) BASED ON ELECTRONIC MODULE (E-MODUL) - Dhani Agusni Zakaria; Septiana Rama Adha; Kurnia Dedi (Lembaga Penelitian Universitas Pasundan, 2018)
Abstract Learning through the implementation of personalizedof instruction module(PSI) models based on digital modules is one of the learning models that can replace the traditional learning process or teacher-oriented learning to the learning process in the modern era which focuses on student-oriented learning or learning student-centered. This study aims to determine whether the implementation of themodel personalized system of instruction (PSI)based on electronic modules (e-module) can affect the mastery of basic motion of basketball, especially in junior high school students. This study uses an experimental method with the design used, namely pre post test control group, with a total sample of 40 students in which 20 students as the experimental group and 20 students as the control group. The research instrument used is the basic motion control sheet on basketball games which consists of mastering basic movements of passing, shooting and dribbling. For the duration of treatment, there are 5 meetings with the duration of each meeting for 3 x 40 minutes. The results of this study are themodels personalized system of instruction (PSI)based on digital modules (E-MODUL) capable of influencing the mastery of students' basic movements in basketball games. Keywords: Model personalized system of instruction (PSI) based on digital modules; Basic Motion; Basketball Games.